The Effect of Local Wisdom Based Learning Media on Science Process Skills in Straight Motion Material - Novita Orab; Abdul Haris Odja; Supartin Supartin; Tirtawaty Abdjul (SEJ (Science Education Journal), 2023)
The purpose of the study was to determine the use of local wisdom-based learning media on science process skills in straight motion material in junior high school. This study used a two-group experimental design, namely between the experimental group and the control group. Sampling in this study used a random sampling technique to determine the class that would be the experimental group and the control group. The population in this study were all students of class VIII who collected 62 students consisting of 2 classes, namely class B and C of SMP Negeri I Marisa, Pohuwato Regency, Gorontalo Province. The results obtained that the effect of learning using media based on local wisdom in terms of increasing the ability of students' science processes on the material of straight motion. This is indicated by the average value of the Post-test for both classes, namely the Experiment class of 85.34 and the control class of 64.73, in addition, based on the results of tcount of 6.60 which is greater than ttable, which is 2.80 meaning Ha is accepted and H0 is rejected and the significant value is obtained by 0.000 <0.005 so that it is obtained that the Local Wisdom-Based Media has an effect on the Science Process Ability of Students at SMP Negeri 1 Marisa.